Association of bull semen protein estimates and SDS-PAGE profiles on semen freezability (Indian Journal of Biochemistry and Biophysics (IJBB), 2023)
It is vital to identify the ejaculate with good freezability by determining the biochemical makeup of the ejaculate at the pre-freeze stage. The present study targeted to assess the use of the protein estimates and profiles at the pre-freeze stage as markers of freezability in Frieswal populations. Storing the proteins for proteomic studies is always tricky in the case of animal studies, where accessibility to liquid nitrogen is limited. Hence alternative storing approaches need to be optimized. The second part of this study examined the protein concentration and protein profiles of RNALater and frozen stored sperm cells to assess the use of RNALater preservation in sperm proteomic studies. Sperm and seminal plasma protein concentrations were quantified using Bradford assay, and total protein quantities were derived. The seminal plasma and sperm protein profiles were generated with SDS-PAGE. The protein estimates and SDS-PAGE profiles of good and poor freeze-groups were similar. Also, sperm and seminal plasma protein concentration were not correlated with the semen volume and sperm count. Even though the yield was comparatively less, the protein profiles of sperm preserved by RNALater were similar to that of frozen sperms. The present study results indicate that the protein estimates and qualitative profiles of sperm and seminal plasma proteins may not be sufficient to reveal the differences in the proteome of good and poor freezable bulls at the macro level. Hence, the protein estimates and profiles of neat semen may not be helpful for the prediction of freezability at the pre-freeze stage. Secondly, this study indicates that RNALater preservation helps store sperms for proteome analysis studies.